Quantitative easing in the euro area: Transmission channels and risks - Klaus-Jürgen Gern; Nils Jannsen; Stefan Kooths; Maik Wolters (Intereconomics, 2015)
The ECB's recently launched Expanded Asset Purchasing Programme is similar to the quantitative easing programmes undertaken by the US Federal Reserve, the Bank of England and the Bank of Japan. While theory suggests that quantitative easing can stimulate economic growth and spur inflation via several transmission channels, the empirical evidence is ambiguous and does not support strong stimulating effects, in particular for the current situation in the euro area. In addition, there are various risks and unintended consequences that may materialise in the medium or long run.
Keywords: 330; Öffentliche Anleihe; Geldpolitische Transmission; Eurozone